IMPROVING PERFORMANCE THROUGH CULTURAL TRANSFORMATION - Edy Saputra; Kiki Farida Ferine; M. Isa Indrawan (Universitas Efarina, 2025)
This study aims to analyze the effect of Implementation of Occupational Health and Safety Management System (OHSMS) and Maturity Level of Occupational Health, Safety, and Environment (K3L) on Performance Achievement, with Cultural Transformation as an intervening variable at PT. PLN (Persero) UP3 North Medan. The study involved 130 respondents selected using purposive sampling. Data analysis was conducted using Partial Least Square Structural Equation Modeling (PLS-SEM) to test the validity, reliability, and relationships among the research variables. The results indicate that both OHSMS implementation and K3L Maturity Level have a positive and significant effect on Performance Achievement, both directly and indirectly through Cultural Transformation as a mediator. Furthermore, Cultural Transformation significantly mediates the relationship between OHSMS implementation and K3L Maturity Level on Performance Achievement, thus enhancing the effectiveness of the OHSMS and K3L systems in improving organizational performance. This study provides practical implications for the management of PT. PLN (Persero) UP3 Medan Utara to continue improving OHSMS implementation, developing K3L Maturity Level, and strengthening Cultural Transformation as a strategy to enhance employee performance. The study also contributes theoretically by reinforcing empirical evidence of Cultural Transformation's mediating role in the context of occupational health and safety.